ANALISIS STRATEGI PENGEMBANGAN BISNIS DENGAN PENDEKATAN BUSINESS MODEL CANVAS DAN SWOT - Agustiani, Windy Eka; Isharina, Ikhtiara Kaideni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The phenomenon of fast fashion makes people highly consumptive in order to keep up with the current trend, but this behavior is environmentally unfriendly. One of the efforts to reduce the impact of fast fashion is reselling used clothes. The objective of this research is to identify the strength, weakness, opportunity, and threat of a business that are going to be sued to create a business plan. This qualitative research was conducted to grip certain understanding about the application of Business Model Canvas (BMC) and SWOT Analysis at Secondhand.jbg. the instrument of analysis is the Business Model Canvas (BMC), while SWOT analysis was used to identify the company’s internal and external conditions. Following the discovery of the internal and external factors, SWOT was employed to do to matching. The data of this research was acquired from interviews, observation, and documentation at the research site, i.e. Secondhand.jbg’s store. This study finds that the company needs to remake its business model using the Future Business Model Canvas. In the run, the shop is advised to run its business plan to develop its entire functional aspects in order to face the competition.